A comprehensive analysis of process-related CO2 emissions from Iran's cement industry - Bahman Massoumi Nejad; Sara Enferadi; Robbie Andrew (Cleaner Environmental Systems)
Direct emissions from the cement industry account for 7%–8% of global anthropogenic CO₂ emissions, primarily from thermal decomposition of carbonates (i.e., calcination) during clinker production. Iran ranks among the world's top ten cement producers and is the seventh-largest CO₂ emitter globally. Despite its significant contribution to global emissions, Iran's process-related CO2 emissions (i.e., chemically derived CO2 from calcination) remain underreported in international datasets. This study addresses this gap by analyzing CO₂ emissions from carbonate decomposition in 77 Iranian cement plants from 2013 to 2023, highlighting regional and plant-specific emission factors. Utilizing plant-specific clinker data, the study applied methodologies aligned with the 2006 IPCC Guidelines and the WRI/WBCSD Greenhouse Gas Protocol to calculate emission factors and CO2 emissions. The findings show notable geographical variations and a substantial national trend, with emissions rising from 28.75 million tonnes (Mt) in 2016 to 39.33 Mt in 2023. A primary contributor is Iran's high clinker-to-cement ratio, averaging 94.1% in 2023, underscoring the urgent need for sustainable production practices, particularly through the adoption of supplementary cementitious materials (SCMs) like pozzolans and industrial by-products. To address this, the study recommends a two-pronged policy approach: reducing clinker content in cement by promoting blended alternatives, such as Portland Composite Cement (PCC) and Portland Pozzolana Cement (PPC), through regulatory controls and economic incentives. These results emphasize the importance of targeted, data-driven policies for sustainable cement production, offering critical insights for stakeholders and policymakers aiming to align Iran's cement sector with global emissions reduction goals.